Desenvolvimento de compósitos poliméricos flexíveis com alta constante dielétrica obtidos a partir de polímeros baseados em pvdf e da perovskita ncbcto - Marcomini, André Luís (Universidade Federal de São Carlos, 2018)
The objective of this thesis was to produce polymer/perovskite based composites to be used as supercapacitors; the composites were made by incorporating an specified type of perovskite (Na1/3Ca1/3Bi1/3Cu3Ti4O12, NCBCTO) with high real dielectric permittivity (~104) (“high k”) in polyvinylidene difluoride (PVDF) and in poly(vinylidene fluoride-co-trifluoro ethylene), P(VDF-co-TrFE). NCBCTO was synthetized by three routes: solid state solution reaction (SSS), combustion synthesis (SCS) and polymer precursor synthesis (PPS). The influence of each synthesis in the final characteristics of the perovskite were also evaluated. Phase purity, particle size and dielectric properties were measured. These analyses allowed to choose the SSS route as the one to produce the perovskite to be incorporated to the polymer matrix. Also, multi walled carbon nanotubes (MWCNT) were incorporated to some samples to promote an easier polarizability and avoid losses. PVDF is a semi-crystalline thermoplastic with different polymorphic phases, each phase having different dielectric properties. Therefore, the influence of the amount of each phase in the final dielectric permittivity was studied. The composites were prepared by casting solution using dimethylformamide (DMF) as solvent. At the end of this process, flexible films were obtained. It was observed that the NCBCTO influences the nucleation of the α, β and γ phases in PVDF. The β phase was the highest in all the samples with NCBCTO; this behavior was attributed to the restricted movements the NCBCTO particles produced in the macromolecules. For the copolymer the crystalline phase was always β at all conditions.
Development of flexible nanocomposites with high dielectric permitivitty using pvdf based polymers and ncbcto perovskite
Keywords: Supercapacitor; PVDF; Perovskita; Polímeros fluorados; Compósitos; Alta permissividade; Perovskite; Fluorinated polymers; Composites; High-permittivity; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS